Recent Progress on the Phase Stabilization of FAPbI3 for High‐Performance Perovskite Solar Cells. Issue 10 (9th August 2022) - Cui, Xiaxia; Jin, Junjun; Tai, Qidong; Yan, Feng
Abstract : With the advantages of narrow bandgap and excellent thermal stability, fomamidinium lead triiodide (FAPbI3 ) perovskite holds the promise to boost the power conversion efficiency (PCE) of perovskite solar cells (PSCs) to over 25%. However, such a promise is blurred by the poor structural stability of the black α‐phase FAPbI3, as it can spontaneously transform into photoinactive δ‐phase at room temperature and this process can be accelerated by the ambient moisture. The incorporation of small ions such as cesium (Cs + ), methylammonium (MA), and bromide (Br − ) into the perovskite lattice is proven to be successful in stabilizing the α‐phase FAPbI3 ; however, the resultant mixed perovskites suffer the phase segregation problem, which inevitably undermines the long‐term stability of the corresponding PSCs. Therefore, continuous efforts are made to realize stable and pure‐phase α‐FAPbI3 perovskites. Herein, the recent progress on the development of efficient and stable FAPbI3 PSCs is summarized with a focus on the different phase stabilization strategies. In addition, the challenges and possible directions for future study are proposed. Abstract : Research progress on the development of efficient and stable FAPbI3 perovskite solar cells is reviewed with a focus on the strategies for stabilizing the phase of α‐FAPbI3 . In detail, solvent engineering, composition engineering, additive engineering, as well as other approaches are discussed systematically. Finally, the challenges and development prospects for future study are proposed.